Penguatan Strategi Marketing Umkm D&D Handycraft Melalui Branding Produk Dan Design Di Wilayah Sentul, Kota Blitar - Putri Kurniawati; Ririt Iriani Sri S; Mohammad Wahed (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
In developing Micro, Small, and Medium Enterprises (MSMEs) it is necessary to have a strategy in marketing its products that aims to increase competitiveness and increase in business development, one of which is through branding so that it has its own distinctive characteristics when compared to MSMEs whose businesses are the same and can also be recognized wider by society. This service aims to provide reinforcement to the community's creative industries (MSMEs) in the Sentul area, Kepanjenkidul District, Blitar City regarding marketing strategies through product branding and design. The methods used in this service activity are direct presentations, discussions, and mentoring. Strengthening this marketing strategy was carried out for three days which coincided at the D&D Handycraft UMKM Shop which was witnessed by the shop owner. For the smooth running of this community service activity, the East Java "Veteran" UPN KKN team made a presentation of material in the form of a PowerPoint which discussed general product branding and design using the Canva application and prepared a tool, namely a camera to take product photos.